Trends in Maternal Mortality in Tertiary Care Hospital, Peshawar Pakistan- A Follow up study - Fouzia Fahim, Waleed Bin Fahim, Farzana Burki, Mehnaz Raees, Gul Lakhta, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To describe the trends in maternal mortality in tertiary care hospitals in the last five years and compare the mortalities in the previous ten years. Methods: All pregnant women from January 2016 to December 2020 were analyzed. The primary outcome of this research was maternal mortality ratios. Various causes of maternal mortality were also evaluated. The correlation between maternal characteristics and maternal mortality was inspected using logistic regression models. Pregnancy outcomes of mothers who died versus mothers who survived were also evaluated. Results: One hundred seventy-three maternal deaths were noted in 49283 pregnant women in 2016-2020. The average maternal mortality ratio in 5 years period was 409 per 100,000 live births. It showed a decreasing curve over the five years, from 539/100,000 live births in 2016 to 295 in 2020. Five year clusters also demonstrated a falling trend, from 856/100,000 live births to 409. Hemorrhage (34.68%), hypertensive disorders of pregnancy (21.38%), suspected cases of thromboembolism (20.80%) were the leading causes of maternal mortality. Pregnancy outcomes in mothers who survived and who expired were evaluated. Almost 33% of maternal deaths had stillbirths as compared to 4.69% in alive mothers (RR 6.87); similarly, unknown outcomes (RR7.56) and ectopic pregnancies (RR 3.01) were more frequent in cases of maternal demise. Conclusion: Trends in maternal mortality show a decreasing curve. Hemorrhage remains the leading cause. Attainment of SDGs requires interventions both at primary and tertiary health care. Keywords: Maternal mortality and Maternal Mortality Ratio (MMR), trends, causes of maternal mortality.